A critical analysis of South Africa’s domestic nexus requirements for the taxation of cross-border services - Dunjane, Kate (Department of Finance and Tax, 2020)
The taxation of cross-border services has for a long time been a contentious topic of discussion across the international tax arena. The controversy of this debate stems predominantly as a result of the long held notion of the permanent establishment as a nexus requirement for source taxation; in a world where global trade, especially in services, can be significantly conducted without the need to establish a prolonged physical presence in the state of source. This is aided by digital technologies and advancements in telecommunications that enable business activities to be carried on remotely. Thus, significant economic activity can take place in a state without meeting the minimum taxable presence required to justify source-based taxation. The problem is that with cross-border transactions between developed and developing countries, where the developing country is typically a capital-importer of services, that developing country will never have the jurisdiction to tax active service-based business income, since the threshold relied on is high, relative to how global trade is conducted today, as it is predominantly dependent on satisfying a physical presence requirement. This study examines the nexus requirements contained in South Africa’s domestic legislation for the taxation of service fee income earned by non-residents. The analysis highlights how the threshold relied on to justify source-based taxation in South Africa is high, since it requires the physical presence of the service provider within the Republic. The study further highlights how South Africa’s policy choice in this regard is akin to a residence-based taxation system, by drawing parallels with the OECD model, which is renowned for its suitability to net capitalexporting and developed economies. Alternative proxies used to tax cross-border services, as noted in the United Nation’s Article 12A, the SADC Model Treaty and the domestic legislation of some BRICS member states, are introduced to the study as comparatives. The general finding hereon is that these alternative nexus requirements are predominantly akin to a policy choice slanted towards source-based taxation, contrasted by the residence-based approach evident in South Arica’s policy choice. Furthermore, the study conducts an analysis of the development of the taxation system in South Africa. The analysis reveals that South Africa’s policy choice to tax active income was largely influenced by the desire to ensure that South African tax laws were internationally compatible at the time when the South African economy was reintegrated with the global economy, postdemocratisation of the Republic. This led to the introduction of the permanent establishment 6 concept into South African domestic law, notwithstanding the knowledge of a not too distant future, where global trade would be conducted via digital technologies and telecommunications, which would render the requirement for physical presence to conduct trade obsolete. The objective of the study is to provide policy recommendations that support a gravitational pull towards more of a territorial-based taxation system. The impact thereof is envisaged to contribute to the strengthening of South Africa’s domestic source rules; the broadening of South Africa’s tax base and the enhancement of the competitiveness of South Africa’s economy.